2021
DOI: 10.3389/fonc.2021.751567
|View full text |Cite
|
Sign up to set email alerts
|

EPDR1, Which Is Negatively Regulated by miR-429, Suppresses Epithelial Ovarian Cancer Progression via PI3K/AKT Signaling Pathway

Abstract: Epithelial ovarian cancer (EOC) is the main pathological type of ovarian cancer. In this study, we found that ependymin-related 1 (EPDR1) was remarkably downregulated in EOC tissues, and low EPDR1 expression was associated with International Federation of Gynecology and Obstetrics (FIGO) stage, metastasis, and poor prognosis. We confirmed that EPDR1 overexpression dramatically suppressed EOC cell proliferation, migration, and invasion in vitro and in vivo. Mechanistically, EPDR1 inhibited EOC tumorigenesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The study suggested that miRNAs may be regulated by the tumor microenvironment, including hypoxia, and are involved in regulating hypoxia-induced responses [31]. Interestingly, EPDR1 expression is reduced in hypoxic BC cells and several studies have shown that its expression is regulated by miRNAs [26,27]. In this study, it was hypothesized that the reduction of EPDR1 might be associated with hypoxia-induced miRNAs.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The study suggested that miRNAs may be regulated by the tumor microenvironment, including hypoxia, and are involved in regulating hypoxia-induced responses [31]. Interestingly, EPDR1 expression is reduced in hypoxic BC cells and several studies have shown that its expression is regulated by miRNAs [26,27]. In this study, it was hypothesized that the reduction of EPDR1 might be associated with hypoxia-induced miRNAs.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, EPDR1 exerts inhibitory effects in ovarian cancer and BC. Zhao et al confirmed that EPDR1 was downregulated in epithelial ovarian cancer (EOC) tissues and its overexpression significantly inhibited the proliferation, migration, and invasion of EOC cells and associated with the inhibition of PI3K/AKT signaling pathway [26]. Liu et al verified the similar oncogenic role of EPDR1 in ovarian cancer [27].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…ENSG00000086289 and ENSG00000133110 were found to be common between diabetes, apolipoprotein, placenta, hepatic, myocardial and prostate datasets. The gene ENSG00000086289 EPDR1 (Ependymin Related 1) may play a role in calcium-dependent cell adhesion that associates various types of cancer includes (15)(16)(17)(18) and the gene ENSG00000133110 Periostin (POSTN) encodes a secreted extracellular matrix protein that functions in tissue development and regeneration, including wound healing, and ventricular remodeling following myocardial infarction. Further it binds to integrins to support adhesion and migration of epithelial cells that plays a role in cancer stem cell maintenance and metastasis (19)(20)(21).…”
Section: Resultsmentioning
confidence: 99%